Central venous access device‐related infections in patients with haemophilia. Issue 3 (26th February 2013) - Yeoh, Zhi Han; Furmedge, Janine; Ekert, Julia; Crameri, Joe; Curtis, Nigel; Barnes, Chris
<x xml:space="preserve">Abstract</x> Aims Fully implantable central venous access devices (CVADs) can offer long‐term reliable venous access to facilitate regular factor replacement therapy in haemophilia. However, CVAD‐related infection remains a major deterrent to the optimal use of CVAD in this population. This report represents the first review of CVAD use in haemophilia in Australia and aims to examine the rate of complications including CVAD‐related infections. Methods A retrospective review of medical records was conducted of all haemophilic patients with fully implantable CVADs at the Royal Children's Hospital (RCH), Melbourne, between 1 June 1992 and 30 June 2009. CVAD‐related bloodstream infection was defined based on the guidelines from the Centre of Disease Control and Victoria National Nosocomial Infection Surveillance. To further enhance identification of CVAD‐related infection in this study, a third criterion of 'suspected infection' was added by the authors. Results Eighty‐one CVADs in 56 patients were managed at the RCH during this time period resulting in a combined study period of 94 756 CVAD days. Median age at first CVAD insertion = 2.16 years (range 0.66 to 13.98 years). CVADs were inserted predominantly due to difficult venous access and prophylaxis initiation (70.4%). Median life‐span of a CVAD was 1227 days, equivalent to 3.36 years (n = 50; range 0.22 to 9.44 years). Fifty‐seven CVAD‐related infections occurred in 37 CVADs (46.3%) in 29 patients (51.8%). Overall incidence of confirmed CVAD‐related bloodstream infection = 0.42 per 1000 CVAD days (95% confidence interval (CI): 0.31 to 0.58 per 1000 CVAD days) and indicate better performance compared with the published benchmark of 0.66 per 1000 CVAD days (0.44 to 0.97 per 1000 CVAD days). The incidence of both confirmed (criteria 1, 2) and suspected (criterion 3) CVAD‐related infection is 0.60 per 1000 CVAD days (95% CI: 0.46 to 0.78), which is comparable to the international benchmark. The majority of CVAD‐related infections (73.7%) were successfully treated with intravenous antimicrobials without necessitating CVAD removal. Klebsiella pneumoniae was the most common organism found in positive blood cultures. Conclusion CVAD‐related infection in this Australian population was comparable to rates described in the medical literature. Ongoing surveillance for infection rates is important to provide an up‐to‐date assessment of risks associated with CVAD use in this population.